2020
DOI: 10.1186/s13006-020-00307-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cortisol and lipids in human milk

Abstract: Background: Human breast milk is one of the key early postnatal biological exposures for the developing child. It includes bioactive compounds, such as cortisol and fatty acids, which may be linked via the mother's lipid metabolism. Methods: This study investigated the associations between cortisol and lipids in human milk at the infant age of 2.5 months. Human milk cortisol concentrations were measured using luminescence immunoassay, and two groups of milks (n = 50 each) were formed based on either high (> 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 64 publications
0
14
2
Order By: Relevance
“…In contrast, a study from the Netherlands reported that breastmilk cortisol increased from two to 12 weeks of lactation [ 20 , 41 ]. Cortisol levels observed in our study were higher than those observed in other studies [ 6 , 10 , 15 , 19 , 21 , 22 , 23 , 24 , 41 , 42 ], but lower than those reported in some studies [ 7 , 20 , 43 ]. Moreover, we observed significant differences between cortisol levels between the season of sample collection—higher levels of cortisol were observed in samples collected during the autumn-winter season in the first month of lactation, but in the sixth month of lactation in the spring-summer season.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In contrast, a study from the Netherlands reported that breastmilk cortisol increased from two to 12 weeks of lactation [ 20 , 41 ]. Cortisol levels observed in our study were higher than those observed in other studies [ 6 , 10 , 15 , 19 , 21 , 22 , 23 , 24 , 41 , 42 ], but lower than those reported in some studies [ 7 , 20 , 43 ]. Moreover, we observed significant differences between cortisol levels between the season of sample collection—higher levels of cortisol were observed in samples collected during the autumn-winter season in the first month of lactation, but in the sixth month of lactation in the spring-summer season.…”
Section: Discussioncontrasting
confidence: 88%
“…According to the lactational programming hypothesis, they affect metabolic and neurobiological development, and, in consequence, offspring phenotype and behavior [ 13 , 14 , 15 , 16 ]. Studies investigated maternal psychological [ 10 , 15 , 17 , 18 , 19 , 20 , 21 , 22 ], socio-demographic [ 7 , 10 , 18 , 23 ], or anthropometric [ 3 , 10 , 24 ] determinants of breastmilk GCs levels provide inconclusive results. Similarly, results regarding the mode of delivery [ 5 , 10 ], preterm birth [ 6 , 10 , 17 ] or seasonal variations [ 10 , 23 ] were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group further showed that variations in these milk components were collectively associated with differences in the microbial community structures of infant feces and the abundance of specific taxa (Pace et al 2021). Finally, Linderborg et al (2020), showed that higher milk cortisol concentrations are related to a greater abundance of lauric and myristic fatty acids. These correlational studies suggest that individual milk components are inter-related and potentially influence one another.…”
Section: Interactions Among Milk Constituentsmentioning
confidence: 92%
“…Recent studies show correlations between different human milk components, including amino acids, sugars, lipids, proteins, hormones, HMOs, and milk microbiota (Gómez-Gallego et al 2018;Linderborg et al 2020;Moossavi et al 2019a;Williams et al 2017;Pace et al 2021). Gómez-Gallego et al (2018), showed that lactate, creatine, proline, lacto-N-fucopentaose 1, 2′-fucosyllactose and very low-density lipoprotein particles were positively correlated with gammaproteobacteria and negatively correlated with alphaproteobacteria, betaproteobacteria and bacilli.…”
Section: Interactions Among Milk Constituentsmentioning
confidence: 99%